PENGARUH ROLE CONFLICT DAN ROLE AMBIGUITY TERHADAP KINERJA AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERASI - Hamdan Husain; Andi Wawo; Puspita Hardianti Anwar (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to study the impact of role conflict and role ambiguity on the performance of auditors with emotional intelligence as the moderator (study conducted in public accounting firms in Makassar and Gowa Regency). This research is a quantitative research. The population in this study are auditors working in the Makassar City area and Gowa Regency. The sampling technique uses random sampling. The sample in this study amounts to 56 auditors. The data used is raw data. Data analysis adopts multiple regression analysis and adjusted regression analysis with absolute difference method. The research results show that role conflict and role ambiguity have a significant negative impact on auditor performance. The analysis of the moderating variables by the absolute difference method shows that emotional intelligence cannot adjust the role conflict and role ambiguity in auditor performance.